Hacia una pedagogía de lectura y escritura: un estudio de género discursivo / Towards a Pedagogy of Academic Reading and Writing: a Discursive Gender Study - de León Arellano, Esperanza; Rodríguez Vázquez, María de Lourdes (Revista Internacional de Aprendizaje en la Educación Superior, 2018)
ABSTRACT This research had the objective of characterizing the rhetorical moves of the research thesis genre at an undergraduate-level from an ecological perspective, within the disciplines of Education and Humanities. Corpus Linguistics was employed as the methodology and an instrument of thirty-five indicators determined its rhetorical-structural characteristics. The analyzed corpus consisted of thirty copies. The results are divided into three sections, structure, characteristics of the sources employed and the rhetorical movements (both obligated and optional) of the theses. Findings in this study can be generalized to the rest of the theses in the faculty, but not to others elaborated in other universities or institutions of higher education. RESUMEN Esta investigación tuvo el objetivo de caracterizar los movimientos retóricos del género de tesis de investigación a nivel pregrado desde una perspectiva ecológica, en disciplinas de Educación y Humanidades. Se empleó la Lingüística de Corpus como metodología y un instrumento con treinta y cinco indicadores para determinar sus características retórico-estructurales. El corpus analizado constó de treinta ejemplares. Los resultados se dividen en tres secciones, estructura, características de las fuentes empleadas y movimientos retóricos (obligados y opcionales) de las tesis. Los hallazgos de esta investigación pueden ser generalizados al resto de tesis de la facultad, pero no a las producciones elaboradas en otras Universidades o Instituciones de Nivel Superior.